A Cross-species Model of Dual-Task Walking in Young and Older Humans and Rats - Hernandez, Abbi R.; Winesett, Steven P.; Federico, Quinten P.; Williams, Sonora A.; Burke, Sara N.; Clark, David J. (Frontiers in Aging Neuroscience, 2020)
Introduction Dual-task walking is common in daily life, but becomes more difficult with aging. Little is known about the neurobiological mechanisms in the brain affecting competing cognitive demands. Translational studies with human and animal models are needed to address this gap. This pilot study investigates the feasibility of implementing a novel cross-species dual-task model in humans and rats, and seeks to establish preliminary evidence that the model induces a dual-task cost. Methods Young and older humans and rats performed an object discrimination task (OD), a baseline task of typical walking (baseline), an alternation turning task on a Figure-8 walking course (Alt), and a dual-task combining object discrimination with the alternation task (AltOD). Primary behavioral assessments including walking speed and correct selections for object discrimination and turning direction. In humans, left prefrontal cortex activity was measured with functional near infrared spectroscopy (fNIRS). Results Human subjects generally performed well on all tasks, but the older adults exhibited a trend for slowing of walking speed immediately prior to the turning decision for Alt and AltOD compared to baseline. Older adults also had heightened prefrontal activity relative to young adults for the Alt and AltOD tasks. Older rodents required more training than young rodents to learn the alternations task. When tested on AltOD with and without a 15-second delay between trials, older rodents exhibited a substantial performance deficit for the delayed version on the initial day of testing. Discussion This study demonstrates feasibility in implementing a cross-species dual-task model, and preliminary evidence of dual-task cost in both humans and rats. The magnitude of effects were small, likely due to the high functional status of both older humans and rats, as well as the relative ease of each task. Future versions of this test should make the tasks more challenging.